Deformation and fracture behaviors of graded 2 titanium ultra-thin metallic sheets in water cavitation micro-forming. (November 2022) - Yu, Chao; Wang, Yun; He, Peiyu; Li, Fuzhu; Li, Ruitao
Water cavitation micro-forming (WCMF) with high quantum efficiency and excellent accuracy are essential for the applications in micro-forming. In this study, based on the size effects, an effective regulation of the cavitation micro-forming was realized. Surprisingly, micro-forming of graded 2 titanium ultra-thin metallic sheets was retained at field of special forming with WCMF. Based on the Hugoniot Elastic Limit of the material, the deformation and fracture behaviors of the case were effectively modified via water-jet shock time varying. In addition, the relationship between the deformation and the fracture of the material and the obtained water-jet cavitation shock time was established. Particularly, the cavitation energy displayed a high efficiency (within 90 s) and have a significant contribution to the appearance of the parabolic dimples. Therefore, this work opens up new opportunities for the development of special forming with excellent micro-forming performance through manipulation of water-jet cavitation shock time.